Nutritional status of children, inmates of a small institution for homeless children in the capital of the State of S. Paulo, Brazil Estado nutritional de crianças internadas em um pequeno orfanato particular na capital do Estado de São Paulo, Brasil - Donald Wilson; Maria José Roncada; Rosa Nilda Mazzilli; Maria Lucia F. Cavalcanti; Dino B. G. Pattoli (Universidade de São Paulo, 1980)
Nutritional surveys (food consumption, clinical and biochemichal) were conducted in a small institution for homeless children. Results showed that only 30% of the children presented adequate calorie intake. Most of the children presented adequate protein intake, but almost half consumed less than 2/3 of the calcium RDA considered necessary. Food handling, processing, and distribution also proved inadequate and wastage, high. Skinfold measurement showed up one case of obesity. Furthermore, most of the children presented clinical signs of vitamin A deficiency, mostly skin lesions; while about half presented clinical signs of riboflavin deficiency. Biochemical data showed that 63.6% had deficient plasma levels of vitamin A, none showed abnormal results for riboflavin excretion, four showed packed blood cell volume below normal, and all had normal hemoglobin levels. Stool examinations revealed a high rate of pathogenic protozoa (Hymenolepis nana), in fact, one of the highest in Brazilian literature. Foram realizados, em um pequeno orfanato, inquéritos nutricionais (alimentar, clínico e bioquímico) cujos resultados mostraram que 30% das crianças tinham ingestão inadequada de calorias, metade ingestão inadequada de cálcio e todas ingestão adequada de proteínas. A manipulação, o processamento e a distribuição dos alimentos eram inadequados e o desperdício era alto. Mais da metade das crianças apresentaram peso abaixo dos padrões, mas a maioria estava acima de 90% para altura, segundo idade. A medida da prega cutânea revelou apenas uma criança obesa. Com relação à vitamina A, a maioria das crianças revelou sinais clínicos atribuíveis à hipovitaminose A, predominantemente sinais cutâneos. Cerca de metade dos examinados revelou sinais de arriboflavinose. Foi baixo o número de crianças que apresentaram sinais clínicos de carência de proteína, ferro e ácido ascórbico. Os dados bioquímicos revelaram que 63,6% das crianças apresentavam níveis séricos abaixo do normal, enquanto que todas apresentaram excreção normal de riboflavina. Com relação à anemia, apenas 4 crianças apresentaram hematócrito abaixo do normal mas todas apresentaram níveis normais de hemoglobina. Os exames de fezes mostraram coeficientes altos para protozoários e Hymenolepis nana, um dos mais altos da literatura brasileira.